Sexual behavior according to undergraduate students: perspective of cross-cultural nursing and intersectional framing - Laércio Deleon de Melo; Thelma Spindola; Cristina Arreguy-Sena; Paula Krempser; Juliana de Lima Brandão; Cristiane Maria Amorim Costa; Felipe Eduardo Taroco; Paulo Ferreira Pinto (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to discuss undergraduate students' sexual behavior from the perspective of social markers and cross-cultural care proposed by Madeleine Leininger. Methods: descriptive-exploratory qualitative research, with a theoretical-philosophical foundation in the Transcultural Theory. Convenience sample was composed of 57 young people from two universities in Rio de Janeiro. The focus groups' content were analyzed lexically using the IRAMUTEQ software. Results: four classes emerged: Young people's sexual scripts: between the fear of an unplanned pregnancy and the risk of exposure to sexually transmitted infections; Affective relationships: trust in steady sexual partners, apparent sense of security and disuse of condoms; Sexual practices, gender and cultural determinants: distinction in men's and women's role; Sexual partnerships, negotiation of condom use and vulnerability to sexually transmitted infections. Final considerations: challenges are perceived for the attention to undergraduate students' sexual health, who verbalized risky sexual behaviors due to sociocultural vulnerabilities.